2020
DOI: 10.1177/0885066620930994
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Acute Kidney Injury in Combat-Injured Patients Associated With Concomitant Vancomycin and Extended-Spectrum β-Lactam Antibiotic Use

Abstract: Background: Multidrug-resistant infections complicating combat-related trauma necessitate the use of broad-spectrum antimicrobials. Recent literature posits an association between vancomycin (VANC) and piperacillin–tazobactam (VPT) combination therapy and acute kidney injury (AKI). We examined whether therapy with VPT was associated with an increased risk of AKI compared to VANC and other broad-spectrum β-lactam antibiotics (VBL) following combat-related injuries. Methods: Patients within the Trauma Infectious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Among these, 261 studies were excluded for the following reasons: evaluating antibiotics other than vancomycin ( n = 104), evaluating outcomes other than AKI ( n = 45), not assessing risk factors ( n = 68), not original articles ( n = 4), involving paediatric patients ( n = 8), involving nonhuman subjects ( n = 12), overlapping study population ( n = 3), not a patient‐level analysis ( n = 1), involving patients who underwent renal replacement therapy ( n = 4), and data extraction not possible or feasible ( n = 12). Finally, 53 studies were included in the meta‐analysis 6–8,10–12,21–67 . A flow diagram summarizing the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, 261 studies were excluded for the following reasons: evaluating antibiotics other than vancomycin ( n = 104), evaluating outcomes other than AKI ( n = 45), not assessing risk factors ( n = 68), not original articles ( n = 4), involving paediatric patients ( n = 8), involving nonhuman subjects ( n = 12), overlapping study population ( n = 3), not a patient‐level analysis ( n = 1), involving patients who underwent renal replacement therapy ( n = 4), and data extraction not possible or feasible ( n = 12). Finally, 53 studies were included in the meta‐analysis 6–8,10–12,21–67 . A flow diagram summarizing the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that these studies minimize the confounding by indication that is typical when the comparator group comprises patients receiving VAN monotherapy. The results of the studies are summarized in Table 1 [ 9 , 10 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. According to these studies, patients treated to the TZP–VAN combination regimen are 1.2–9.5 times more likely to develop AKI compared to those receiving FEP–VAN or MER–VAN combinations.…”
Section: Epidemiology Of Tzp Plus Van-associated Akimentioning
confidence: 99%
“…Piperacillin-tazobactam and cefepime are commonly added to vancomycin for empiric antipseudomonal coverage in healthcare-associated infections. Recent studies have shown an increased risk of AKI when vancomycin is combined with piperacillin-tazobactam in comparison to other agents [6,7]. In a study by Navalkale et al, it was shown that the incidence of AKI was higher with the combination of vancomycin-piperacillintazobactam therapy when compared with vancomycin-cefepime therapy [8].…”
Section: Introductionmentioning
confidence: 99%